2021
DOI: 10.1136/annrheumdis-2021-220262
|View full text |Cite
|
Sign up to set email alerts
|

Response to: ‘Correspondence on ‘Lupus or not? SLE Risk Probability Index (SLERPI): a simple, clinician-friendly machine learning-based model to assist the diagnosis of systemic lupus erythematosus’ by Batuet al

Abstract: We would like to thank Batu et al 1 for the interest in our work and for evaluating the performance of SLE Risk Probability Index (SLERPI) 2 in paediatric SLE patients. In their analysis using the simple scoring version of the index as a binary outcome, the sensitivity and specificity was 90.0% and 81.2%, respectively. 1 Applying a more stringent cut-off of >8 resulted in a sensitivity of 81.2% and a specificity of 89.4%. Notably, the area under the receiver operating characteristic curve of the scoring versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…In the European population, the sensitivity, specificity and accuracy of this model were estimated at 94.2%, 94.4% and 94.2%, respectively. 9 Another study from Australia suggested that this model has high sensitivity (98.5%) but low specificity (84.6%). 10 Due to differences in diagnostic performance with the existing classification criteria to diagnose patients with SLE in different races, 11 12 the performance of SLERPI should be further validated in other races.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the European population, the sensitivity, specificity and accuracy of this model were estimated at 94.2%, 94.4% and 94.2%, respectively. 9 Another study from Australia suggested that this model has high sensitivity (98.5%) but low specificity (84.6%). 10 Due to differences in diagnostic performance with the existing classification criteria to diagnose patients with SLE in different races, 11 12 the performance of SLERPI should be further validated in other races.…”
Section: Introductionmentioning
confidence: 97%
“…Based on common clinical and serological features, Adamichou et al recently developed a new, simple and interpretable model, the Systemic Lupus Erythematosus Risk Probability Index (SLERPI), to help diagnose SLE early. 9 This model includes 14 variably weighted items, with >7 patients being classified as SLE. In the European population, the sensitivity, specificity and accuracy of this model were estimated at 94.2%, 94.4% and 94.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%